Evaluation of the Properties of Calotropis procera Oil Aiming the Production of Biodiesel - de Sousa, Lindeberg Ventura; Santos, Adriana Paula Batista; Di Souza, Luiz; Santos, Anne Gabriella Dias; Beatriz, Adilson (Orbital: The Electronic Journal of Chemistry, 2018)
Heavy consumption of non-renewable raw materials and/or renewable energy production produces environmental imbalance. Thus, the search for a means of sustainable and environmentally appropriate life requires scientific research in new renewable biofuels. The Calotropis procera, exotic oilseed widely distributed is a hardy shrub well suited to the northeast that produces seeds with oil. So, in this work were made fruit collection, drying, extraction and analysis of physical, chemical and thermal properties of oil aiming its use in biodiesel synthesis. The oil was extracted with Soxhlet method and characterized through physical-chemical, thermal analysis, and FTIR and NMR spectroscopy analysis. The results indicate that it is possible to obtain 21% ± 2 by weight of an oil physicochemical quality within the standard recommended by the legislation, except for the acid value was high and indicates that the best way to transesterification it is to make the catalyzed by acid or heterogeneous. The thermal analysis showed that the oil has high purity and is constituted by two material strips of different mass or molecular structures and has high thermal stability and convenient for the synthesis reaction. FTIR and NMR spectroscopy confirmed that the major compounds present in the oil are saturated and unsaturated fatty acids. DOI: http://dx.doi.org/10.17807/orbital.v10i2.1061